Euripides-Rezeption in Kaiserzeit und Spätantike - Schramm, Michael (Millennium-Studien / Millennium Studies, 2020)
During the Imperial Rome Age and late antiquity, Euripides was considered a tragic dramatist par excellence, and, alongside Homer, was the most frequently cited poet. This book examines the reception of complete and partially transmitted Euripidean tragedies into the Greek language vis-à-vis key authors and literary genres of the Imperial Rome Age and late antiquity, situating them in the cultural and literary-historical context of the times.